Analysis of references used in scientific papers published in Peruvian medical journals, 2005 - 2008 - Huamaní, Charles (2012)
Background: Bibliographic references support our investigations. Analysis of their use identifies both the information socialization process and how it is built. Objective: To describe bibliography source characteristics that support published investigations in Peruvian biomedical journals. Design: Bibliometric study. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Bibliographic material: Scientific articles published during 2005-2008 identified in SciELO Peru’s database. Interventions: Only scientific articles were selected, identifying references used and building a database where citation analysis was performed. Main outcome measures: Frequencies, percentages, obsolescence index and Price index. Results: Analysis of 493 articles included 12 475 references; 79% (9 837) consisted in scientific articles citations, 26 journals had 25% (2 458) of citations (four Peruvian journals, one from Brazil and 21 of English language) y 2 406 had the other 75% (7 379) citations; 51% of references were six years old or less, and 35% five or less. Conclusions: Most information used to generate scientific articles came from scientific journals, centered in a small nucleus (26 journals), mostly in English language but with presence of Peruvian journals.